Stroke: Medium and long-term mortality and associated factors in French-speaking West Africa, case of Benin - GNONLONFOUN, DIEU-DONNÉ; ADJIEN, KODJO CONSTANT; Ossou-Nguiet, Paul Macaire; Avlessi, Isaac; Goudjinou, Gérald; Houannou, Octave; ACAKPO, Jocelyn; Houinato, Dismand; AVODE, DOSSOU GILBERT (My University, 2014)
Introduction: Stroke is the leading cause of mortality and physical disability in sub-Saharan Africa. Objective: Determining medium-term and long-term mortality for stroke and identifying associated factors. Method: It consists in a cross-sectional, prospective, descriptive and analytical study that was conducted from April 1 to August 31, 2013 in the Neurology Department of CNHU-HKM in Cotonou. It involved patients who have known stroke for at least 6 months, and were all admitted and discharged later on. The disease survivors were re-contacted and examined again at home or at hospital. Then, the number of deceased was systematically recorded with precision of death time-limit. Results: The overall mortality rate was 29%. Mortality was higher with patients over 70 years with a frequency of 57.1%. The medium-term mortality rate was 25% against 4% for long-term. The average time-limit for death occurrence after the vascular incident was 7 months ± 6.4 months. Prognostic factors of mortality were: the age of the patient (IC95% = 7.73 [1.49 - 39.99], p = 0.015 ), marital status (IC95% = 0.27 [0.08 to 0.94], p = 0.039 ) and the presence of aphasia (IC95% = 5.52 [1.45 to 20.94 ], p = 0.012). Conclusion: Stroke mortality still remains significant, even after the patients have been discharged from hospital. A good psychological family support and efficient aphasia coverage are essential for its reduction.
Keywords: Stroke; Medium; mortality; associated factors; West Africa; Benin